Specific patterns of allergic sensitization in early childhood and asthma & rhinitis risk. Issue 2 (18th January 2013) - Stoltz, D. J.; Jackson, D. J.; Evans, M. D.; Gangnon, R. E.; Tisler, C. J.; Gern, J. E.; Lemanske, R. F.
Summary Background Specific patterns of allergic sensitization as well as quantification of the in vitro IgE response in early life may provide relevant clinical insight into future rhinitis and asthma risk. Objective To define relationships among established sensitization to particular aeroallergens, quantitative analyses of allergen‐specific IgE levels, pet exposure and sensitization, and asthma and rhinitis risk. Methods Children at high‐risk for the development of asthma and allergic diseases were enrolled at birth into the Childhood Origins of ASThma (COAST) study. Allergen‐specific IgE was assessed at ages 1, 3, 6, and 9 years by fluoroenzyme immunoassay (Unicap® 100; Pharmacia Diagnostics). Current asthma and rhinitis were diagnosed at age 6 and 8 years. Results Sensitization to dog was strongly associated with increased asthma risk (P < 0.0001). Sensitization to perennial compared with seasonal allergens was more strongly associated with asthma risk, while sensitization to seasonal allergens was more closely associated with rhinitis risk. Increased levels of specific IgE to perennial allergens were associated with an increased asthma risk (P = 0.05), while any detectable level of IgE to seasonal allergens was associated with increased rhinitis risk (P = 0.0009). While dog and cat sensitization were both independently associated with increased asthma and rhinitis risk, dog exposure at birth was associated with a reduced risk of asthma, regardless of dog sensitization status during the first 6 years of life (P = 0.05). Conclusions and Clinical Relevance Analysing specific patterns of an individual's allergic sensitization profile reveals additional relevant associations with asthma and rhinitis risk as opposed to the information gained from characterizing an individual as 'atopic' by the presence of any demonstrable sensitization alone. Furthermore, protective mechanisms of dog exposure with regards to asthma risk appear to be unrelated to the prevention of sensitization.